The Effect of Knowledge-Oriented Leadership and Reward on Employee Performance in Bantar Gebang MSMEs - Joy Benjamin Rafael; Yuningsih Yuningsih; Lis Andriani (International Forum of Researchers and Lecturers, 2026)
MSMEs can play a significant role in bolstering a community's economy, with their growth highly dependent on workforce performance. Effective leadership and appropriate incentives significantly enhance employee productivity, motivation, and engagement. The purpose of this study is to ascertain how employee performance in MSMEs in the Bantar Gebang market is impacted by knowledge-oriented leadership and incentives. 135 employees of MSMEs in the Bantar Gebang market were given paper questionnaires to complete in order to gather data. Validity and reliability tests were performed using SPSS version 27 for data analysis in this study. CFA with KMO, Anti-Image, and Factor Loading was used for the validity test; Kolmogrov-Smirnov was used for the normalcy test; multiple linear regression and t-tests were used for hypothesis testing. The findings supported hypothesis 1 by demonstrating that knowledge-oriented leadership significantly and favorably affected worker performance. Additionally, the data supported hypothesis 2 by demonstrating that rewards significantly and favorably impacted employee performance. Employees need to be encouraged by MSMEs leaders to expand their knowledge and abilities through a variety of experiences. MSMEs must put in place extra incentive programs to show their staff how much they are valued. MSMEs owners are required to evaluate and recognize staff members who exhibit strong initiative and go above and beyond the call of duty.